Primary and secondary prevention of skin cancer in mountain guides: attitude and motivation for or against participation. (20th June 2018) - Zink, A.; Thomé, F.; Schielein, M.; Spinner, C.D.; Biedermann, T.; Tizek, L.
Abstract: Background: Outdoor professionals such as mountain guides are at a substantial risk of developing non‐melanoma skin cancer (NMSC) due to solar ultraviolet radiation (UVR) exposure. Despite major recent primary prevention efforts, studies on secondary skin cancer prevention efforts are limited and corresponding data on outdoor workers scarce. Objective: To assess the sun protective behaviour and individual motivations for or against skin cancer screening examinations in the German mountain guide population to aid in the development of effective awareness and prevention strategies. Methods: A cross‐sectional study among all registered mountain guides in Germany was conducted using a 35‐item online questionnaire on primary and secondary prevention of NMSC as well as perceived barriers for prevention. Results: A total of 145 mountain guides participated in the study in January 2017. Of these, 86.2% reported using sunscreen often or always, 62.1% with a sun protection factor (SPF) of 30–50% and 60.7% had undergone dermatological examination by a medical professional. The most common reasons for using secondary prevention efforts were hope of an early diagnosis (77.3%), fear of skin cancer (73.9%) and the intention to be aware of one's own health (70.5%). The main reasons for not doing so were absence of conspicuous skin conditions (63.2%) and feeling healthy (59.6%). Conclusion: Awareness of prevention strategies recommended by the scientific community is low among affected occupationally high‐risk mountain guide populations. Understanding the specific needs of this high‐risk group is essential for the development of sustainable awareness and prevention strategies.